METHODS AND TECHNOLOGIES OF USING DOCUMENTARY SOURCES IN HISTORY LESSONS IN SECONDARY SCHOOL - Македонський, Карл; Михайлюк, Віталій (SWorldJournal, 2024)
The article considers current issues of theoretical, methodological and practical use of documentary sources on the study of history in secondary school. The subject of the study was the scientific works of historians-methodologists, experienced and young